Organizational and Supervisor Support on Turnover Intention Mediated by Affective Commitment - Indra, Ikhsan Prasetya; Sudiro, Achmad; Rofiq, Ainur (Interdisciplinary Social Studies, 2023)
Background: A company's sustainability lies in managing its human resources. Human resources are one of the critical elements for the achievement of company goals. The company's success or failure depends on employees' job satisfaction (Individually) which affects the overall job satisfaction of the organization. Aim: This study is about the effect of organizational support and supervisor support against turnover intention mediated by affective commitment. Method: This research uses a quantitative approach with an explanatory research design. The research site is the Lima Puluh Kota County Fire Service. The population in this study, namely freelance daily employees (PHL) in the Lima Puluh Kota District Fire Service, has 100 employees in  Lima Puluh Kota District of 2022. Research sampling techniques that use saturated sampling. The primary data in this study were respondents' answers through the distribution of questionnaires. While the secondary data is obtained from the object. The analysis techniques were descriptive analysis, PLS analysis, and structural model analysis before finally going through hypothesis testing and mediation Findings: The results showed a significant negative influence between supervisor support for turnover intention and affective commitment mediation, meaning that the higher the supervisor's support, the higher the affective commitment, and will indirectly reduce the occurrence of employee turnover intention.